PATTERN OF STROKE IN DIABETICS AND NON-DIABETICS - Ali, Rashid; Kazmi, Sumera; Iqbal, Muhammad Zafar (Journal of Ayub Medical College Abbottabad, 2013)
Background: Diabetes mellitus has been established as a risk factor for stroke. Diabetes increases the risk of stroke in younger patients and diabetics aremore likely to have an ischemic stroke. There are numerous studies on microvascular complications but there are only a few studies on strokes in diabetics. Therefore, this study was conducted to assess the impact of diabetes on the pattern of stroke in our population. Methods: This descriptive study was carried out in Department of Medicine, Ayub Teaching Hospital, Abbottabad from September 2011 to February 2012. Forty diabetics and 40 non-diabetics stroke patients were included in the study. Risk factors were noted and their distribution in both groups was analysed. Results: The difference in age and gender distribution in both groups was not significant. Thirty-four (85%) of diabetics, and 25 (62.5%) non-diabetics suffered from ischemic stroke. Six (15%) of diabetics and 15 (37.5%) of non-diabetics suffered from haemorrhagic stroke. The differences between the distribution of ischemic stroke were significant (p<0.02). In the diabetic group 32.5% of the individuals suffered from lacunar infarcts and in the non-diabetic group 10% suffered from lacunar infarctions (p<0.02). There was no significant difference in distribution of risk factors. Conclusion: Diabetics are more likely to have an ischemic stroke and lacunar infarctions. Keywords: Diabetes mellitus, Stroke, Lacunar infarcts